PENGARUH LINGKUNGAN KERJA DAN INSENTIF TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PABRIK KELAPA SAWIT PT. PERKEBUNAN NUSANTARA V SEI ROKAN - Audina, Mia; Andri, Seno (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study aims to determine how the environment influences the work (service employees, working conditions, and employee relations) and incentives (material and non-material incentives) to the productivity of employees at mills PT. PTPN V Sei Rokan.The population in this study are employees at mills PT. Plantation Nusantar V Sei Rokan by taking a sample of 63 people.From the results analsisis data covering Validity, reabilitias, and multiple linear regression, the results showed no significant influence among the working environment on produktivias working with the calculated t (6.895)> t table (2.000) and there was a significant effect of incentives on productivity working with the calculated t (4.443)> t table (2,000) and is based on the simultaneous test concluded that the work environment and incentives together have a significant effect on employee productivity by 53.7% the amount of influence.Keywords:Work Environment, incentives and labor productivity